1992
DOI: 10.1093/intimm/4.10.1137
|View full text |Cite
|
Sign up to set email alerts
|

Novel cell junctions induced by activating Thy-1-specific antibodies

Abstract: KT16, like other anti-Thy-1 antibodies, induces T cell aggregation. Protein A-gold labelling shows the antibody to be concentrated along areas of intercellular contacts. Electron micrographs of KT16 treated T cells reveal a consistent type of junction between the cells. We demonstrate that this type of cell junction is Thy-1 specific, is predominantly the property of antibodies directed against a particular epitope, and is distinct from cellular aggregation caused by concanavalin A or anti-CD3 antibodies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…2b, right) and 5a-8 (data not shown)]. Therefore, MCS-34 recognized epitope A, like G7 and KT16 (Millrain et al, 1992). These results indicate that MCS-34 exhibits the same ability to recognize Thy-1 glycoprotein as G7 and KT16.…”
Section: Recognition Site Of Mcs-34 On Thy-1 Glycoproteinmentioning
confidence: 76%
See 3 more Smart Citations
“…2b, right) and 5a-8 (data not shown)]. Therefore, MCS-34 recognized epitope A, like G7 and KT16 (Millrain et al, 1992). These results indicate that MCS-34 exhibits the same ability to recognize Thy-1 glycoprotein as G7 and KT16.…”
Section: Recognition Site Of Mcs-34 On Thy-1 Glycoproteinmentioning
confidence: 76%
“…These special antiThy-1 MAbs may have a capacity to aggregate by themselves because the F(ab')z fragment of KT16 induces T-cell growth only in the presence of a second antibody (Millrain et al, 1992). These anti-Thy-1 MAbs are known to recognize both Thy-1.1 and Thy-1.2 (Millrain et aL, 1992), and the recognized epitope is designated Thy-1A (Pont et aL, 1985). We therefore examined 9 of our established anti-Thy-1 MAbs for their recognition capability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). It has been reported that T-cell proliferation induced by G7 is correlated with the ability to induce cell-cell aggregation (Millrain et al, 1992). Although G7 alone could aggregate CS-21 cells, MCS-34 alone could not aggregate them.…”
Section: Discussionmentioning
confidence: 94%